Probiotic Bacteria Alter Pattern-Recognition Receptor Expression and Cytokine Profile in a Human Macrophage Model Challenged with Candida albicans and Lipopolysaccharide - Matsubara, Victor H.; Ishikawa, Karin H.; Ando-Suguimoto, Ellen S.; Bueno-Silva, Bruno; Nakamae, Atlas E. M.; Mayer, Marcia P. A. (Frontiers in Microbiology, 2017)
Probiotics are live microorganisms that confer benefits to the host health. The infection rate of potentially pathogenic organisms such as Candida albicans, the most common agent associated with mucosal candidiasis, can be reduced by probiotics. However, the mechanisms by which the probiotics interfere with the immune system are largely unknown. We evaluated the effect of probiotic bacteria on C. albicans challenged human macrophages. Macrophages were pretreated with lactobacilli alone (Lactobacillus rhamnosus LR32, L. casei L324m or L. acidophilus NCFM) or associated with E. coli lipopolysaccharide (LPS), followed by the challenge with C. albicans or LPS in a co-culture assay. The expression of pattern-recognition receptors genes (CLE7A, TLR2, and TLR4) was determined by RT-qPCR, and dectin-1 reduced levels were confirmed by flow cytometry. The cytokine profile was determined by ELISA using the macrophage cell supernatant. Overall probiotic lactobacilli down-regulated the transcription of CLEC7A (p<0.05), resulting in the decreased expression of dectin-1 on probiotic pretreated macrophages. The tested Lactobacillus species down-regulated TLR4, and increased TLR2 mRNA levels in macrophages challenged with C. albicans. The cytokines profile of macrophages challenged with C. albicans or LPS were altered by the probiotics, which generally led to increased levels of IL-10 and IL-1β, and reduction of IL-12 production by macrophages (p<0.05). Our data suggest that probiotic lactobacilli impair the recognition of PAMPs by macrophages, and alter the production of pro/anti-inflammatory cytokines, thus modulating inflammation.